Les migrations inter-communales en Suisse: un "effet-montagne" ? - Martin Camenisch; Bernard Debarbieux (Revue de Géographie Alpine)
Eager to go beyond existing publications on intercommunal migrations in Switzerland, this paper focuses on a comparison of behaviors between communes of different types: ruralm urban, mountain, touristic, etc. It is based on two set of data: the Swiss Population Census (1999-2008) and the Swiss Household Panel. The main conclusions of this paper are twofold: first, contrary to the dominant practice which compare communes according to their respective difference between in-migration and out-migration rate, this paper highlights the contrast between "warm" and "cold" communes (comparing the migration rate itself); the is a "mountain factor" which means that most intercommunal migrations occur within the mountain zone, or within the Swiss Plateau.